Crenças sobre sexualidade entre estudantes de Medicina: uma comparação entre gêneros - Lima, Maria Cristina Pereira [UNESP]; Cerqueira, Ana Teresa De Abreu Ramos [UNESP] (Associação Brasileira de Educação Médica, 2008)
OBJECTIVE: Gather information about sex knowledge and sexuality among medical students for analyzing differences related to gender and study year. METHODS: A structured questionnaire was applied to students of the School of Medicine of Botucatu, composed by questions about sexuality and sexual activity. The questionnaire was applied in class and 455 students agreed to participate in the study. The analysis was stratified by gender and study year using chi-square test. RESULTS: A comparison of data obtained from first-year and final-year students revealed an increase in the frequency of active sex life, but not in satisfaction. Beliefs predominate over misbeliefs, with differences among gender. Female sexuality and homosexuality-related aspects however have revealed a significant percentage of erroneous answers. CONCLUSIONS: There still exists disinformation about specific issues of human sexuality among medical students. Medical education thus needs to address sexuality in its multiple aspects for enabling the students to deal with the sexuality of their patients.

OBJETIVO: Identificar informações sobre sexualidade entre estudantes de Medicina e analisar as diferenças quanto a gênero e ano do curso. MÉTODO: Foi aplicado um questionário estruturado a estudantes da Faculdade de Medicina de Botucatu, com questões sobre sexualidade e vida sexual dos sujeitos. A aplicação ocorreu em sala de aula, sendo que 455 estudantes (82,6%) aceitaram participar do estudo. A análise foi estratificada para gênero e ano do curso, sendo utilizado o teste do qui-quadrado. RESULTADOS: Comparando-se primeiros e últimos anos, observou-se aumento da freqüência de vida sexual ativa, mas não de satisfação. Crenças predominaram sobre crendices, tendo sido observadas diferenças entre os gêneros. Aspectos da sexualidade feminina e da homossexualidade apresentaram um significativo percentual de respostas equivocadas. CONCLUSÕES: Entre estudantes de Medicina ainda persiste desinformação sobre aspectos específicos da sexualidade humana. A formação médica precisa abarcar a sexualidade em seus múltiplos aspectos, capacitando os profissionais a lidarem com a sexualidade de seus pacientes.
Beliefs about sexuality among medical students: a comparison between gender
Keywords: Medical Education; Sexuality; Students, Medical; Beliefs; Educação Médica; Sexualidade; Estudantes de Medicina; Crenças